2017
DOI: 10.1007/s11356-017-9383-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular responses of the earthworm Eisenia fetida to polychlorinated biphenyl contamination in soil

Abstract: Polychlorinated biphenyls (PCBs) are a class of man-made organic compounds ubiquitously present in the biosphere. In this study, we evaluated the toxic effects of different concentrations of PCBs in two natural soils (i.e. red soil and fluvo-aquic soil) on the earthworm Eisenia fetida. The parameters investigated included anti-oxidative response, genotoxic potential, weight variation and biochemical responses of the earthworm exposed to two different types of soils spiked with PCBs after 7 or 14 days of exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This method is fast and can determine quantitative changes in the levels of metabolites, such as amino acids and sugars, provoked by an external stressor [26,27,28,29,30]. Being an untargeted technique, such an analysis can be reproduced accurately across different laboratories [31,32,33,34,35,36], providing insights into the reaction of the organism to an external source of stress, its molecular endpoints in terms of changes in metabolite levels, and in depicting the mode of toxicity of the contaminants [37].…”
Section: Introductionmentioning
confidence: 99%
“…This method is fast and can determine quantitative changes in the levels of metabolites, such as amino acids and sugars, provoked by an external stressor [26,27,28,29,30]. Being an untargeted technique, such an analysis can be reproduced accurately across different laboratories [31,32,33,34,35,36], providing insights into the reaction of the organism to an external source of stress, its molecular endpoints in terms of changes in metabolite levels, and in depicting the mode of toxicity of the contaminants [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies denoted the induction of DNA damage to coelomocytes of E. fetida exposed to soil spiked with a standard PCB mixture at 0.25 mg kg À1 d.w. [186]. Dose-dependent increases of the ROS-scavenging enzymes (catalase, superoxide dismutase, and peroxidase) were also found in PCB-spiked soils, without signs of lipid peroxidation [186]. Similarly, Shen et al [187] also found increased activity of antioxidant enzymes in earthworms exposed to field soils contaminated with PCBs.…”
Section: Effect Of Polychlorinated Biphenyls At Sub-organism Levelmentioning
confidence: 94%
“…There is a paucity of new approaches on PCB toxicity to terrestrial invertebrates. Recent studies denoted the induction of DNA damage to coelomocytes of E. fetida exposed to soil spiked with a standard PCB mixture at 0.25 mg kg À1 d.w. [186]. Dose-dependent increases of the ROS-scavenging enzymes (catalase, superoxide dismutase, and peroxidase) were also found in PCB-spiked soils, without signs of lipid peroxidation [186].…”
Section: Effect Of Polychlorinated Biphenyls At Sub-organism Levelmentioning
confidence: 98%
“…In all studies, DNA damage assessment was conducted on coelomocytes – hemocytes of the annelids that can be recovered from the coelomic fluid with non-invasive techniques by submerging the organism in ethanol 5% saline solution that might be integrated with the chelating agent EDTA and the mucolytic agent guaiacol or similar. The studies explored the potential genotoxic effect of a broad set of chemicals including as insecticides Cyantraniliprole ( Qiao et al, 2019 ), Acetamiprid ( Li B. et al, 2018 ), Neonicotionoids ( Chevillot et al, 2017 ), Imidacloprid ( Wang et al, 2016 ), Spirotetramat ( Zhang et al, 2015 ), Thiacloprid ( Feng et al, 2015 ), and Guadipyr ( Wang et al, 2015 ) that represented the most numerous, followed by fungicides Pyraclostrobin ( Ma et al, 2019 ), Fluoxastrobin ( Zhang et al, 2018 ), Tebuconazole ( Chen et al, 2018 ), and a smaller set referred to herbicides Tribenuron ( Chen et al, 2018 ) and Mesotrione ( Li X. et al, 2018 ) or general pesticides including Polychlorinated biphenyls ( Duan et al, 2017 ) and natural toxins used as biofumigants ( Fouché et al, 2016 ) and copper sulfide ( Mincarelli et al, 2019 ) that is one of the few chemical treatments allowed in organic farming. In all studies, synthetic compounds were studies at increasing doses of exposure normally below 10 mg/kg of soil, with the exception of the insecticide Guadipyr ( Wang et al, 2015 ) that was used between 10 and 100 mg/kg of soil.…”
Section: Critical Analysis Of the Scientific Literaturementioning
confidence: 99%
“…DNA damage was often related to markers of oxidative stress that exhibited a similar trend in response to pollutants. This is central in describing the mechanism of genotoxicity of pesticides that often is mediated by an increase in cellular reactive oxygen species formation due to cellular impairment ( Zhang et al, 2015 , 2018 ; Duan et al, 2017 ; Li B. et al, 2018 ; Li X. et al, 2018 ; Qiao et al, 2019 ). Interestingly despite the different nature and target of the pesticides tested, a common pattern of response is often evincible in the biological response of Eisenia spp.…”
Section: Critical Analysis Of the Scientific Literaturementioning
confidence: 99%